USING FLASH CARDS TO IMPROVE STUDENTS’ VOCABULARY - Aisyah Siti Khasanah Atmaja; Gina Sonia (PROJECT (Professional Journal of English Education), 2020)
Vocabulary is one of an important thing in English learning that cannot be delivered by people. For get a good ability in listening, speaking, reading and writing, people should be mastering a vocabulary. That is the reason why vocabulary is crucial in language learning and when the researcher establish that vocabulary mastery of Junior High School are less. Then, teaching vocabulary using flashcard chosen as the theme of this classroom action research. The sample of this research was seven grade of junior high school in Katapang. The researcher presented the result and the analysis of data collected that consist of cycle 1 and cycle 2. Each cycle of the research consist of planning, acting, observing and reflecting activities. In the research, there are some steps before cycle 1 and cycle 2, there are observation and pre-test. The last steps after cycle 1 and cycle 2 are post-test. In the pre-test the researcher used the convensional method. Most of students not active and enthusiasm in the lesson in cycle 1.But, when the researcher used flashcard, the student more active and interest. It could be seen in mean score of the post-test in cycle 1, that is 79.50. After that, in th cycle 2, the mean score was 87.50. It was higher that pre-test. Finally, from the researcher explanation concluded based on the qualitative data that consist of pre-test until post-test, that flashcard could advance the students vocabulary.